Aplicação da espectrometria de massas com ionização electrospray no monitoramento de processos oxidativos avançados de interesse ambiental: degradação de fármacos, avaliação de sistemas oxidativos e oxidação do isopreno - Ilza Dalmazio (2007)
Electrospray Ionization Mass Spectrometry (ESI-MS and ESI-MS/MS) was used to monitor reactions taking place in aqueous medium promoted by the advanced oxidation processes (AOPs). The following investigations were performed: degradation of pharmaceuticals (caffeine and tetracycline), characterization of novel oxidation systems (heterogeneous Fenton and H2O2/I-), and oxidation of isoprene induced by hydroxyl radicals. In the monitoring of degradation of caffeine (by TiO2/UV, H2O2/UV and Fenton systems), and tetracycline (by ozonation) products and intermediates were characterized, a number of them not previously reported. In the monitoring of reactions of model organic compounds with the novel oxidation systems, i. e. heterogeneous Fenton (based in magnetite) and H2O2/I-, a number of products, formed as a result of the reaction with hydroxyl radicals, were characterized. These findings thus allowed the classification of such systems as AOPs. In the ESI-MS monitoring of the oxidation of isoprene, under conditions that attempted to mimic the atmospheric environment, poly-oxygenated species were detected and proposed to be key components to the formation of secondary organic aerosols (SOAs). The applicability of the ESI-MS in attaining relevant information on the systems herein evaluated was thus demonstrated. Its potential to furnish key information, which could not be achieved via concurrent techniques, certainly will contribute to expand the knowledge about the AOPs